2015
DOI: 10.1213/ane.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

An Electronic Checklist Improves Transfer and Retention of Critical Information at Intraoperative Handoff of Care

Abstract: An electronic checklist improved relay and retention of critical patient information and clinician communication at intraoperative handoff of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 28 publications
2
66
0
3
Order By: Relevance
“…However, in common with previous findings, 11,13 our study showed handover times of 2 to 3 min which were not prolonged by the implementation of the handover training and display of the checklist. Because a significant number of healthcare providers in our study were concerned about the time required for using the handover checklists, and since this may have been one of the factors explaining why not everybody adopted the protocol, it is important to share this evidence with staff in the hope that this will increase utilisation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, in common with previous findings, 11,13 our study showed handover times of 2 to 3 min which were not prolonged by the implementation of the handover training and display of the checklist. Because a significant number of healthcare providers in our study were concerned about the time required for using the handover checklists, and since this may have been one of the factors explaining why not everybody adopted the protocol, it is important to share this evidence with staff in the hope that this will increase utilisation.…”
Section: Discussionsupporting
confidence: 92%
“…Because a significant number of healthcare providers in our study were concerned about the time required for using the handover checklists, and since this may have been one of the factors explaining why not everybody adopted the protocol, it is important to share this evidence with staff in the hope that this will increase utilisation. The literature 11,12,14–16 shows that successfully implementing a checklist protocol can improve satisfaction, and we found the same.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations